Reimagining dots and dashes: Visualizing structure and function of organelles for high-content imaging analysis. Issue 3 (18th March 2021) - Chin, Marcus Y.; Espinosa, Jether Amos; Pohan, Grace; Markossian, Sarine; Arkin, Michelle R.
Summary: Organelles are responsible for biochemical and cellular processes that sustain life and their dysfunction causes diseases from cancer to neurodegeneration. While researchers are continuing to appreciate new roles of organelles in disease, the rapid development of specifically targeted fluorescent probes that report on the structure and function of organelles will be critical to accelerate drug discovery. Here, we highlight four organelles that collectively exemplify the progression of phenotypic discovery, starting with mitochondria, where many functional probes have been described, then continuing with lysosomes and Golgi and concluding with nascently described membraneless organelles. We introduce emerging probe designs to explore organelle-specific morphology and dynamics and highlight recent case studies using high-content analysis to stimulate further development of probes and approaches for organellar high-throughput screening. Graphical abstract: Abstract : Diseases from cancer to neurodegeneration induce changes in organellar structure and function. Innovative fluorescent probes allow live-cell monitoring of dynamic structural and functional changes by high-content analysis. Chin et al. highlight four organelles that exemplify phenotypic discovery from probe design to high-throughput screening for modulators of organelle function.